Four-year persistence of type-specific immunity after quadrivalent human papillomavirus vaccination in HIV-infected children: Effect of a fourth dose of vaccine. Issue 13 (23rd March 2017) - Levin, Myron J.; Huang, Sharon; Moscicki, Anna-Barbara; Song, Lin-Ye; Read, Jennifer S.; Meyer, William A.; Saah, Alfred J.; Richardson, Kelly; Weinberg, Adriana; ,
Abstract: Objective: Although HIV-infected children are recommended to receive quadrivalent human papillomavirus vaccine (QHPV) there is limited information on their response to QHPV. This study in HIV-infected children, evaluated the magnitude and duration of immune responses to QHPV. This report describes type-specific serum antibody responses over a 4-to-5 year period after either 3 or 4 doses of QHPV. Design/methods: HIV-infected children, ages 7-to-11 years, received 3 doses of QHPV (n = 96) or placebo (n = 30). At 72 weeks QHPV recipients received a fourth dose (n = 84), while placebo recipients began the 3-dose QHPV schedule (n = 27). HPV serotype-specific antibody was determined, by competitive Luminex immunoassay (cLIA) and IgG Luminex immunoassay, at 2, 3.5, and 4-to-5 years after the last dose of QHPV in each treatment arm. Results: At 4-to-5 years after the last dose of QHPV, antibody titers were significantly higher in 4-dose than in 3-dose group. However, the proportion of vaccinees with a seroresponse in the cLIA assay was not different between the two groups (86–93% for HPV types 6, 11, and 16, and 64% for HPV type 18). These results were very similar to the seroresponse rate in these HIV-infected children at 1 month after completing vaccination. Conclusions: Children with well-controlled HIV infection who receive 3 doses of the QHPV vaccine maintain seropositivity and antibody levels that are generally similar to children of the same age who are not HIV-infected. Antibody titer correlated strongly with low log HIV RNA, low CD8%, and high CD4%. Additionally, a fourth dose of vaccine in HIV-infected children produces a marked rise in antibody characteristic of an anamnestic response and persistence of high antibody levels. Study identification: IMPAACT P1085 (V501-021). CLINICALTRIALS.GOV identifier:NCT01206556 .